2014
DOI: 10.1371/journal.pone.0116453
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Protein Network Alterations upon Retinal Ischemia-Reperfusion Injury by Quantitative Proteomics Using a Rattus norvegicus Model

Abstract: Retinal ischemia is a common feature associated with several ocular diseases, including diabetic retinopathy. In this study, we investigated the effect of a retinal ischemia and reperfusion (I/R) injury on protein levels via a quantitative shotgun strategy using stable isotope dimethyl labeling combined with LC-MS/MS analysis. Based on the relative quantitation data of 1088 proteins, 234 proteins showed a greater than 1.5-fold change following I/R injury, 194 of which were up-regulated and 40 were down-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
5
7
0
Order By: Relevance
“…In the retina, the IPL and OPL mostly consist of synapses, which have important roles in communication between neurons. Reduced retinal thickness, especially in the IPL and OPL, has been observed in streptozotocin-induced diabetes (7,41) and I/R injury (42) and in the present study ( Fig. 2C and Supplemental Table S1), with significant down-regulation of synapse-related proteins, such as synaptophysin and synaptotagmin-1, identified by proteomic study of the retina after I/R injury (42).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the retina, the IPL and OPL mostly consist of synapses, which have important roles in communication between neurons. Reduced retinal thickness, especially in the IPL and OPL, has been observed in streptozotocin-induced diabetes (7,41) and I/R injury (42) and in the present study ( Fig. 2C and Supplemental Table S1), with significant down-regulation of synapse-related proteins, such as synaptophysin and synaptotagmin-1, identified by proteomic study of the retina after I/R injury (42).…”
Section: Discussionsupporting
confidence: 77%
“…Reduced retinal thickness, especially in the IPL and OPL, has been observed in streptozotocin-induced diabetes (7,41) and I/R injury (42) and in the present study ( Fig. 2C and Supplemental Table S1), with significant down-regulation of synapse-related proteins, such as synaptophysin and synaptotagmin-1, identified by proteomic study of the retina after I/R injury (42). Thus, it is likely that the dysfunction of synapses due to I/R injury contributes to the reduction of the retinal thickness.…”
Section: Discussionmentioning
confidence: 95%
“…This is consistent with previous studies that have indicated a reduction in the levels of Camkv protein in a rat model of ischaemia reperfusion injury. 57 Besides modulation of heat-shock and cytoskeletal proteins, Ca 2+ binding proteins such as S100A10, S100, FBN1, and LGALS1 were identified to be downregulated and these proteins interact with other downregulated proteins such as ANAX6, ANAX1, APOE, NEK9, MFAP2, and HSPG2. This interconnected network was largely downregulated; however, synaptic vesicle glycoproteins 2A and 2C, that have direct interaction with HSPG2, and KNG1 that interacts with Anxa1, were significantly enriched.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies documented that mTOR can be the therapeutic target in various ischemic diseases [5658]. A recent proteomics study reported that mTOR pathway was suppressed after retinal I/R injury, further delineating the protective role of mTOR [59]. It has been reported that increasing mTOR phosphorylation was neuroprotective against ischemic brain injury [58] and this prompt us to speculate that lutein not only protects the retinal Műller cells from hypoxia-induced apoptosis but also autophagy, possibly by targeting mTOR-associated pathway and improving cell survival against hypoxic injury.…”
Section: Discussionmentioning
confidence: 99%